Flow induced microvascular network formation of therapeutic relevant arteriovenous (AV) loop-based constructs in response to Ionizing radiation - Schmidt, Volker-Jürgen; Köpple, Christoph; Bigdeli, Amir Khosrow; Kneser, Ulrich (Medical science monitor, 2017)
Background: The arteriovenous (AV) loop model enables axial vascularization to gain a functional microcirculatory system in tissue engineering constructs in vivo. These constructs might replace surgical flaps for the treatment of complex wounds in the future. Today, free flaps are often exposed to high-dose radiation after defect coverage, according to guideline-oriented treatment plans. Vascular response of AV loop-based constructs has not been evaluated after radiation, although it is of particular importance. It is further unclear whether the interposed venous AV loop graft is crucial for the induction of angiogenesis. Material/Methods: We exposed the grafted vein to a single radiation dose of 2 Gy prior to loop construction to alter intrinsic and angio-inductive properties specifically within the graft. Vessel loops were embedded in a fibrin-filled chamber for 15 days and radiation-induced effects on flow-mediated vascularization were assessed by micro-CT and two-dimensional histological analysis. Results: Vessel amount was significantly impaired when an irradiated vein graft was used for AV loop construction. However, vessel growth and differentiation were still present. In contrast to vessel density, which was homogeneously diminished in constructs containing irradiated veins, vessel diameter was primarily decreased in the more peripheral regions. Conclusions: Vascular luminal sprouts were significantly diminished in irradiated venous grafts, suggesting that the interposing vein constitutes a vital part of the AV loop model and is essential to initiate flow-mediate angiogenesis. These results add to the current understanding of AV loop-based neovascularization and suggest clinical implications for patients requiring combined AV loop-based tissue transfer and adjuvant radiotherapy.